New surfactant protein C gene mutations associated with diffuse lung disease - Guillot, L; Epaud, R; Thouvenin, G; Jonard, L; Mohsni, A; Couderc, R; Counil, F; de Blic, J; Taam, R A; Le Bourgeois, M; Reix, P; Flamein, F; et al. (Journal of medical genetics, 2009)
Background:Mutations in the surfactant protein C gene (SFTPC) have been recently associated with the development of diffuse lung disease, particularly sporadic and familial interstitial lung disease (ILD).Objective:We have investigated the prevalence and the spectrum of SFTPC mutations in a large cohort of infants and children with diffuse lung disease and suspected with surfactant dysfunction.Method and results:121 children were first screened for the common SFTPC mutation, p.Ile73Thr (I73T). Ten unrelated patients were shown to carry this mutation. The I73T mutation was inherited in six cases, and appeared de novo in four. The 111 patients without the I73T mutation were screened for the entire coding sequence of SFTPC. Of these, eight (seven unrelated) subjects were shown to carry a novel mutant allele of SFTPC. All these seven new mutations are located in the BRICHOS domain except the p.Val39Ala (V39A) mutation, which is in the surfactant protein C (SP-C) mature peptide.Conclusions:Our results confirm that SFTPC mutations are a frequent cause of diffuse lung disease, and that I73T is the most frequent SFTPC mutation associated with diffuse lung disease.